2023
DOI: 10.3390/jcm12196354
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Microbiota in Naïve Keratoconus: A Multicenter Validation Study

Carlos Rocha-de-Lossada,
Cosimo Mazzotta,
Federico Gabrielli
et al.

Abstract: In the field of Ophthalmology, the mNGS 16S rRNA sequencing method of studying the microbiota and ocular microbiome is gaining more and more weight in the scientific community. This study aims to characterize the ocular microbiota of patients diagnosed with keratoconus who have not undergone any prior surgical treatment using the mNGS 16S rRNA sequencing method. Samples of naïve keratoconus patients were collected with an eNAT with 1 mL of Liquid Amies Medium (Copan Brescia, Italy), and DNA was extracted and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…6 The Journal of Keratoconus and Ectatic Corneal Diseases has the honor and task of hosting present and future innovations in clinical and surgical research, in keratoconus diagnostics and in everything relating to genetic, hormonal, inflammatory, environmental and biochemical aspects, including new research topic in ocular microbiota. 7,8 All ophthalmologists of good will are invited to contribute with their studies to the success of the IJKECD, owned and managed by Jaypee Brothers Medical Publishers (P) LTD.…”
Section: It Is Time For a Turning Point In Keratoconusmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The Journal of Keratoconus and Ectatic Corneal Diseases has the honor and task of hosting present and future innovations in clinical and surgical research, in keratoconus diagnostics and in everything relating to genetic, hormonal, inflammatory, environmental and biochemical aspects, including new research topic in ocular microbiota. 7,8 All ophthalmologists of good will are invited to contribute with their studies to the success of the IJKECD, owned and managed by Jaypee Brothers Medical Publishers (P) LTD.…”
Section: It Is Time For a Turning Point In Keratoconusmentioning
confidence: 99%
“…6 The Journal of Keratoconus and Ectatic Corneal Diseases has the honor and task of hosting present and future innovations in clinical and surgical research, in keratoconus diagnostics and in everything relating to genetic, hormonal, inflammatory, environmental and biochemical aspects, including new research topic in ocular microbiota. 7,8 All ophthalmologists of good will are invited to contribute with their studies to the success of the IJKECD, owned and managed by Jaypee Brothers Medical Publishers (P) LTD.In recent years we have witnessed and contributed to a revolution in the knowledge of the pathophysiology of keratoconus, of the clinic and of pathophysiological optics, thanks to machines such as Scheimpflug-based and now OCT-based tomography. Furthermore, the biomechanics of the cornea is increasingly closer, especially motion-tracking Brillouin Microscopy, surely it will contribute to many new discoveries and increasingly earlier diagnoses of ectatic diseases.…”
mentioning
confidence: 99%
“…Keratitis is an inflammatory disease of the eye, studies have found that the diversity of ocular surface flora changes when bacterial keratitis occurs [59,60], and intestinal commensal bacteria can affect the susceptibility to ocular keratitis by affecting sIgA levels [61]. Animal models have shown that gut microbiota can provide protection against Pseudomonas aeruginosa-induced keratitis by regulating mature neutrophils.…”
Section: Bacterial Keratitis (Bk)/ Fungal Keratitis (Fk)mentioning
confidence: 99%
“…A healthy surface microbiota is important for proper interaction between the CL and the ocular surface, as well as to reduce the potential occurrence of serious issues during CL wear. [9][10][11] One factor that affects ocular discomfort is lid wiper epitheliopathy (LWE), whose prevalence ranges from 67% to 80% in symptomatic CL wearers, but is less than 32% in asymptomatic wearers. 12 LWE results from the friction of the eyelid over the ocular surface when the tear film thins.…”
Section: Introductionmentioning
confidence: 99%